2000
DOI: 10.1164/ajrccm.162.3.9910037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Methacholine Bronchial Challenge Performed by Auscultation in Young Asthmatic Children

Abstract: The measurement of bronchial reactivity is an important aid in the diagnosis of asthma, but the technique using spirometry is not feasible in young children. The aim of the present study was to determine the efficacy and safety of a modification of the chest auscultation method in the assessment of bronchial reactivity to inhaled methacholine in young asthmatic children. One hundred forty-six young children with asthma (mean age, 4.3 yr) underwent bronchial challenges with nebulized methacholine using the ausc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
79
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 10 publications
15
79
1
1
Order By: Relevance
“…There may be, however, some concern about the safety and applicability of the method we used to assess bronchial responsiveness in young children. 282 Our results were similar to the results described by Springer et al, 226 who found that termination of the bronchial provocation test was accompanied by at least the presence of audible wheeze in 81 per cent of young children with asthma (mean age 4.3 years), compared to 77 per cent in our study, and no severe desaturations were noted. In other studies was shown that occurrence of lung sounds agreed well with a 20 per cent fall in forced expiratory volume in one second during bronchial challenge tests in older children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…There may be, however, some concern about the safety and applicability of the method we used to assess bronchial responsiveness in young children. 282 Our results were similar to the results described by Springer et al, 226 who found that termination of the bronchial provocation test was accompanied by at least the presence of audible wheeze in 81 per cent of young children with asthma (mean age 4.3 years), compared to 77 per cent in our study, and no severe desaturations were noted. In other studies was shown that occurrence of lung sounds agreed well with a 20 per cent fall in forced expiratory volume in one second during bronchial challenge tests in older children.…”
Section: Discussionsupporting
confidence: 92%
“…9,224 Also, interobserver variability was highly acceptable with complete agreement between three observers in 80 per cent of cases. 9 As was concluded by Springer et al, 282 we think that the method that we used to assess bronchial responsiveness is safe, effective, easily applicable and clinically significant. However, further standardization and validation of bronchial challenge tests is required in both healthy and non-healthy children at different ages, but especially in young children.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The end point of a challenge for the EOT positive group (EOT + ) was defined as one or more of the following: (a) audible wheeze over the chest or trachea (provocation concentration of wheezing; PCW + ); (b) oxygen saturation below 91% (provocation concentration of saturation; PCS + ); or (c) respiratory symptoms such as persistent cough, shortness of breath, or tachypnea for which the children were unable to sustain the test (provocation concentration of respiratory symptoms; PCr + ). 4,5 Subjects were defined as EOT negative (EOT − ) if they reached a methacholine concentration of 16 mg/mL without developing these manifestations. Each subject inhaledsolution for 1 minute using a nebulizer (DeVilbiss Health Care Inc., Somerset, PA) and a facemask, continuing every 5 minutes until the maximum concentration or end point was reached.…”
Section: Methacholine Challenge Testingmentioning
confidence: 99%
“…However, young children lack the ability to tolerate the repetitive measurements of bronchial challenge testing with spirometry and thus hindering its clinical use. 3,4 Therefore, other methods have been used clinically to assess bronchial hyperresponsiveness in preschool children, and transcutaneous oxygen tension, 6 as well as other techniques to measure lung function, such as the forced oscillation technique (FOT), 7 the impulse oscillation system (IOS), 8 the interrupter technique, 9 and plethysmography. 10 However, these techniques have some limitations.…”
Section: Introductionmentioning
confidence: 99%